The Mission of an Evangelist - Amsterdam (Mineapolis Word Wide Publications, 2001)
Amsterdam declaration -- A covenant for evangelists -- Church leaders task group report -- Strategists task group report -- Theologians task group report.
Keywords: Evangelistic work -- Congresses. Evangelists -- Congresses. Evangelistic work